1977
DOI: 10.1021/bi00620a022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of oxygen exchange in actin-activated hydrolysis of adenosine triphosphate by myosin subfragment 1

Abstract: The gamma-phosphoryl groups of two intermediates (M-ATP and M-ADP-P1) in the pathway of MgATP hydrolysis by myosin undergo extensive oxygen exchange with water. Actin activates the overall rate of hydrolysis at a rate-limiting step which follows these exchange reactions. Thus, actin, by decreasing the turnover time of hydrolysis, would be expected to proportionately decrease the time available for oxygen exchange. Using subfragment 1 of myosin, the turnover time of hydrolysis can be varied over a wide range by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…After several cycles, ATP undergoes almost complete oxygen exchange with the solvent. This oxygen exchange is also observed in the presence of actin (49) but at a slower rate (55,56), because instead of favoring phosphate rotation, the acto-myosin complex induces product release. The rates and equilibrium constants of the forward and reverse ATP hydrolysis reaction in Dictyostelium myosin II at varying temperatures have been reported (57).…”
Section: Discussionmentioning
confidence: 66%
“…After several cycles, ATP undergoes almost complete oxygen exchange with the solvent. This oxygen exchange is also observed in the presence of actin (49) but at a slower rate (55,56), because instead of favoring phosphate rotation, the acto-myosin complex induces product release. The rates and equilibrium constants of the forward and reverse ATP hydrolysis reaction in Dictyostelium myosin II at varying temperatures have been reported (57).…”
Section: Discussionmentioning
confidence: 66%
“…Shukla & Levy's interpretation of their data differs in important ways from ours aside from questions of equivalence of the phosphate oxygens, and as their conclusions have quite general significance it seems desirable to be explicit as to why our interpretations differ. They conclude that the rate of the step limiting exchange is 1 s-1 (Shukla & Levy, 1977a), which is an order of magnitude slower than the rate of reversal of the cleavage step and thus they are forced to postulate that the rate of rotation is rate limiting. Using our method to analyze their data, we obtain a value of about 20 s-1 for the rate of exchange, which is close to the rate of reversal of the cleavage step determined by other kinetic methods.…”
Section: Discussionmentioning
confidence: 99%
“…This is a plausible interpretation of the data but it has been shown by more direct methods involving the use of highly enriched [ -|80] ATP and the formation of a volatile derivative of the product P¡ for direct mass spectral analysis , that the P¡ oxygens are equivalent2 and that apparent nonequivalence arises from the contribution of a second ATPase pathway to the overall flux. In addition, Shukla & Levy (1977a) from a limited analysis of their data concluded that the maximal rate of intermediate oxygen exchange was slower than expected if the exchange were limited by the rate of reversal of the hydrolytic cleavage step. A more complete analysis given in this paper shows that the discrepancy is much smaller than suggested by Shukla & Levy, although still experimentally significant.…”
mentioning
confidence: 99%
“…Phosphate-water oxygen exchange gives a measure of the rate constant for P¡ release, although interpretation is indirect (Bagshaw & Trentham, 1973). Measurements have been done on isolated proteins (Shukla & Levy, 1977;Sleep & Boyer, 1978; Webb & Trentham, 1981;Evans & Eisenberg, 1989;Bowater et al, 1990) and give a measure of the ratio of the rate constants operating on the ADP-P¡ complex, fc+3/ L•2 in Scheme 1. Most researchers find little or no exchange during ATP hydrolysis at high [actin], suggesting that P, release (fc+3) is several times faster than the ATP reformation rate constant (k_2).…”
mentioning
confidence: 99%